SCARB1 Gene Variants Are Associated With the Phenotype of Combined High High-Density Lipoprotein Cholesterol and High Lipoprotein (a). (October 2016) - Yang, Xiaoping; Sethi, Amar; Yanek, Lisa R.; Knapper, Cathy; Nordestgaard, Børge G.; Tybjærg-Hansen, Anne; Becker, Diane M.; Mathias, Rasika A.; Remaley, Alan T.; Becker, Lewis C.
Abstract : Background—: SR-B1 (scavenger receptor class B type 1), encoded by the gene SCARB1, is a lipoprotein receptor that binds both high-density lipoprotein (HDL) and low-density lipoprotein. We reported that SR-B1 is also a receptor for lipoprotein (a) (Lp(a)), mediating cellular uptake of Lp(a) in vitro and promoting clearance of Lp(a) in vivo. Although genetic variants in SCARB1 are associated with variations in HDL level, no SCARB1 variants affecting Lp(a) have been reported. Methods and Results—: In an index subject with high levels of HDL cholesterol and Lp(a), SCARB1 was sequenced and demonstrated a missense mutation resulting in an S129L substitution in exon 3. To follow up, 2 cohorts (GeneSTAR, the family-based Genetic Study of Atherosclerosis Risk [n=543], and CCHS, the population-based Copenhagen City Heart Study [n=5835]) were screened for combined HDL cholesterol and Lp(a) elevations. Subjects with the extreme phenotype (HDL >80 mg/dL and Lp(a) >100 nmol/L in GeneSTAR, n=8, and >100 mg/dL in CCHS, n=9) underwent sequencing of SCARB1 exons; 15 of 18 from the combined population demonstrated genetic variants, including rare or uncommon missense or splice site mutations in 9 and homozygous synonymous variants in 6. Functional studies with 4 of the SCARB1 variants (c.386C>T, c.631-14T>G, c.4G>A, and c.631-53 m C>T & c.726+55 m CG>CA) showed decreased receptor function in vitro. Conclusions—: Human SCARB1 gene variants are associated with a new lipid phenotype, characterized by high levels of both HDL cholesterol and Lp(a). SCARB1 exonic variants often result in diminished function of translated SR-B1 via reduced binding/intracellular transport of Lp(a). Abstract : Supplemental Digital Content is available in the text.